2021
DOI: 10.1016/j.watres.2021.117003
|View full text |Cite
|
Sign up to set email alerts
|

Biotransformation of lincomycin and fluoroquinolone antibiotics by the ammonia oxidizers AOA, AOB and comammox: A comparison of removal, pathways, and mechanisms

Abstract: In this study, we evaluated the biotransformation mechanisms of lincomycin (LIN) and three fluoroquinolone antibiotics (FQs), ciprofloxacin (CFX), norfloxacin (NFX), and ofloxacin (OFX), which regularly enter aquatic environments through human activities, by different ammonia-oxidizing microorganisms (AOM). The organisms included a pure culture of the complete ammonia oxidizer (comammox) Nitrospira inopinata , an ammonia oxidizing archaeon (AOA) Nitrososphaera gargensis , and an ammonia-oxidizing bacterium (AO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(19 citation statements)
references
References 64 publications
1
13
0
Order By: Relevance
“…Compared with conventional activated sludge, pharmaceutical removal efficiencies can be enhanced by nitrifying systems. This has been demonstrated in lab-scale enriched nitrifying sludge systems, full-scale nitrification processes, and pure nitrifying microorganism reactors. , The positive correlation between pharmaceutical removal efficiency and nitrifying activities proved the significance of cometabolism in biodegradation of pharmaceuticals. ,, Ammonia-oxidizing bacteria (AOB) were capable of cometabolically catalyzing the biodegradation of various organic substrates in the obligatory presence of ammonium, owing to the nonspecific enzyme ammonia monooxygenase (AMO) . Recently, ammonia-oxidizing archaea and a complete ammonia oxidizer (comammox) also showed their abilities in cometabolic biodegradation of pharmaceuticals. , In addition to AOB-induced cometabolism, metabolic biodegradation by microorganisms (e.g., heterotrophs) could also contribute to removal of nontoxic pharmaceuticals, which were utilized as energy and carbon sources …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Compared with conventional activated sludge, pharmaceutical removal efficiencies can be enhanced by nitrifying systems. This has been demonstrated in lab-scale enriched nitrifying sludge systems, full-scale nitrification processes, and pure nitrifying microorganism reactors. , The positive correlation between pharmaceutical removal efficiency and nitrifying activities proved the significance of cometabolism in biodegradation of pharmaceuticals. ,, Ammonia-oxidizing bacteria (AOB) were capable of cometabolically catalyzing the biodegradation of various organic substrates in the obligatory presence of ammonium, owing to the nonspecific enzyme ammonia monooxygenase (AMO) . Recently, ammonia-oxidizing archaea and a complete ammonia oxidizer (comammox) also showed their abilities in cometabolic biodegradation of pharmaceuticals. , In addition to AOB-induced cometabolism, metabolic biodegradation by microorganisms (e.g., heterotrophs) could also contribute to removal of nontoxic pharmaceuticals, which were utilized as energy and carbon sources …”
Section: Introductionmentioning
confidence: 99%
“…This has been demonstrated in lab-scale enriched nitrifying sludge systems, 10 full-scale nitrification processes, 11 and pure nitrifying microorganism reactors. 5,12 The positive correlation between pharmaceutical removal efficiency and nitrifying activities proved the significance of cometabolism in biodegradation of pharmaceuticals. 10,13,14 bacteria (AOB) were capable of cometabolically catalyzing the biodegradation of various organic substrates in the obligatory presence of ammonium, owing to the nonspecific enzyme ammonia monooxygenase (AMO).…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, they pose a risk to the environment, ecology and the health of human beings [ 1 ], especially considering that wastewater treatment plants (WWTPs) were not a priori conceived to handle this kind of pollutants [ 2 ]. In this regard, ciprofloxacin (CIP), a widely used antibiotic, displays inert chemical bonds, which makes CIP very difficult to degrade by microorganisms and remains persistent in wastewater [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ciprofloxacin is the most widely used fluoroquinolone antibiotics due to its activity against a wide range of Gram-negative and Gram-positive bacteria (Davis et al 1996;Picó & Andreu 2007). Zhou et al (2021) found that pure cultures of AOB or ammonia oxidizing archaea (AOA) instead of the complete ammonia oxidizer (comammox) could significantly biotransformed ciprofloxacin and norfloxacin via cometabolism. Although nitrifying bacteria were already known to exhibit remarkable performance in the removal of ciprofloxacin (Dorival-García et al 2013;Wang et al 2017), little information was yet available on the interactions between the AOB activity and fluoroquinolone (e.g., ciprofloxacin) along with its degradation products so far.…”
Section: Graphical Abstract Introductionmentioning
confidence: 99%